A bold fresh piece of humanity - O'Reilly, Bill. (New York : Broadway Books, 2008)
In his most intimate book yet, O'Reilly goes back in time to examine the people, places, and experiences that launched him on his journey from working-class kid to immensely influential television personality and bestselling author. Readers will learn how his traditional outlook was formed in the crucible of his family, his neighborhood, his church, and his schools, and how his views on America's proper role in the world emerged from covering four wars on five continents over three-plus decades as a news correspondent
Keywords: O'Reilly, Bill; Journalists -- United States -- Biography